Image processing & communications challenges 6 - International Image Processing and Communications Conference Bydgoszcz, Poland) 2014; Choras, Ryszard S.; SpringerLink (Online service). (Cham Springer International Publishing, 2015)
This book collects a series of research papers in the area of Image Processing and Communications which not only introduce a summary of current technology but also give an outlook of potential feature problems in this area. The key objective of the book is to provide a collection of comprehensive references on some recent theoretical development as well as novel applications in image processing and communications. The book is divided into two parts and presents the proceedings of the 6th International Image Processing and Communications Conference (IP&C 2014) held in Bydgoszcz, 10-12 September 2014. Part I deals with image processing. A comprehensive survey of different methods of image processing, computer vision is also presented. Part II deals with the telecommunications networks and computer networks. Applications in these areas are considered.
Electronic reproduction.
Keywords: Image processing -- Digital techniques -- Congresses; Artificial intelligence -- Congresses; Software engineering -- Congresses; Electronic books